Hard segment composition, morphology, tensile properties and biostability of linked-macrodiol based siloxane poly(urethane urea). (March 2019) - Dandeniyage, Loshini S.; Adhikari, Raju; Bown, Mark; Shanks, Robert; Adhikari, Benu; Gunatillake, Pathiraja A.
Graphical abstract: Highlights: Linked-macrodiol based siloxane poly(urethane urea)s were synthesised by varying the chain extender composition. Amount of urea and urethane linkages in the hard segment influenced the tensile properties and morphology. Higher amount of 1, 2- ethanediamine formed ordered domains of hard segment. 40–60 mol-% BHTD in the hard segment provided high tear and tensile strengths. Hard segment composition did not significantly affect the oxidative stability. Abstract: A series of siloxane poly(urethane urea)s (SiPUU) was synthesised to investigate variation of the molar ratio of urethane and urea linkages on morphology, tensile properties and in vitro oxidative stability. The soft segments of SiPUU were based on 20:80 (w/w) mixture of 4, 4′-methylenediphenyl diisocyanate (MDI) linked poly(hexamethylene oxide) and α, ω-bis(6-hydroxyethoxypropyl) polydimethylsiloxane. The hard segment content in these formulations was 45% (w/w) and composed of MDI and a mixture of 1, 2- ethanediamine (EDA) and 1, 3-bis(4-hydroxybutyl)-1, 1, 3, 3-tetramethyldisiloxane (BHTD) in varying molar ratios. Six SiPUU with 0, 20, 40, 60, 80 and 100 mol-% of BHTD in the hard segment in combination with EDA were prepared. The synthesized SiPUU were characterized using size exclusion chromatography, Fourier transform infrared (FTIR) spectroscopy, differential scanning calorimetry (DSC), dynamic mechanical analysis (DMA), and tensile testing. The oxidative stability of the SiPUU samples was evaluated by an in vitro oxidative test method using a 20% H2 O2 containing 0.1 mol/L CoCl2 solution on 150% strained dumbbells at 37 °C over a period of 60 days. The results showed that the modulus, tensile and tear strengths increased with increasing proportion of EDA in the hard segment. In SiPUU where the EDA content was 80% and above, a well-ordered hard segment was observed. Scanning electron microscopic (SEM) examination confirmed that the SiPUU containing a mixture of chain extenders were oxidatively stable independent of the chain extender compositions. The SiPUU chain extended only with either BHTD or EDA showed minor surface changes. All SiPUU samples, except the one containing 100% BHTD in the hard segment, showed high ultimate tensile strength (25–35 MPa), elongation (400–870%) and tear strength (40–93 N/mm) with very good oxidative stability.